Investigation of Effect of Bulk Temperature on Dissolution and Participation of Asphaltenes Using Flocculation Onset Titration - Z. A. , Chandio (2013)
All of the organic fouling in petroleum refinery crude preheat train is caused by insoluble asphaltenes and the effect of bulk temperature on solubility of asphaltenes is somewhat uncertain. In this work, the effect of bulk temperature on flocculation and precipitation of asphaltenes in crude oil residue has been investigated at different temperatures from 20 0C to 95 0C using automated flocculation titrimeter. It is observed that the solubility parameter and solvating power of the oil increased with the increase in temperature. The results indicate that solubility of the particles in oil and overall stability of the oil increased with the increase in temperature in the range studied.